Rape Myth Acceptance and Other Barriers to Formally Reporting Sexual Assault Among College Students With and Without Sexual Assault Histories - Lathan, Emma C. (Journal of interpersonal violence, 2023)
Low rates of reporting sexual assault to law enforcement have been attributed to a culture of rape myth acceptance. Yet, rape myth acceptance rates and specific barriers to reporting have not been examined by sexual assault and reporting histories. This study compared the rape myth acceptance levels of reporting survivors, non-reporting survivors, and individuals without sexual assault histories. The sample consisted of 579 undergraduate students (68.0% White, 72.5% women) at a public university in the southeastern U.S. Differences in non-reporting survivors’ experienced barriers to reporting and the perceived barriers of those without sexual assault histories were also examined. Results indicate differences in rape myth endorsement by sexual assault and reporting status, with the highest rape myth adherence rates endorsed by individuals without a sexual assault history and the lowest endorsed by reporting survivors. While non-reporting survivors and those without sexual assault histories shared two of the top three barriers to reporting (i.e., wanted to avoid thinking or talking about it, did not want family or friends to find out), non-reporting survivors were more likely to endorse personal reasons for not reporting, and those without sexual assault histories were more likely to endorse concerns about the law enforcement response to rape. Several barrier factors were identified among non-reporting survivors (i.e., fear of law enforcement involvement, personal reasons, ambiguity of the event, responsibility) and among individuals without sexual assault histories (i.e., risks outweigh benefits, victim blaming, ambiguity). Although both survivors and individuals without sexual assault histories acknowledge the personal, social, and legal risks of reporting a sexual assault to law enforcement, survivors’ experienced barriers differed in nuanced ways from the presumed barriers of individuals without sexual assault histories. Findings may enhance sexual assault prevention trainings and awareness campaigns by targeting both rape myth beliefs and specific barriers to reporting of those with and without sexual assault histories.